“In Other Words, …”: A Corpus-based Study of Reformulation in Judicial Discourse - Mazzi, Davide (HERMES - Journal of Language and Communication in Business, 2011)
The language of the law has been a favourite subject of investigation for both legal professionals and linguists for more than a decade now. Linguists, for instance, have paid increasing attention to the interplay of precise and ﬂexible terms in legal drafting, and language variation across the genres of legal discourse. Among the latter, judgments have been discussed as a case in point by argumentation scholars, although the linguistic components of judicial argumentative discourse have often been overlooked. In the light of this, the aim of this paper is to carry out a corpus-based analysis of the open-ended category of reformulation markers as outstanding discursive items of judicial discourse in two comparable corpora of authentic judgments issued by two different courts of last resort, namely the Court of Justice of the European Communities and Ireland’s Supreme Court. By combining a qualitative with a quantitative analysis, the study shows that reformulation markers tend to activate a variety of discursive conﬁgurations across the two courts. Hence, data reveal that reformulation strengthens the quality of both judicial narrative, as it were – as is clear from its deployment in clarifying the normative background and specifying the factual framework of disputes – and at once judicial argument, when judges characterise, reﬁne or grade reported arguments/interpretations or they wish to make their reasoning more solid and convincing.